Hukum hijab dan cadar Syaikh Abdul Aziz bin Abdullah bin Baz, Syaikh Muhammad bin Shalih Al-Utsaemin ; penerjemah Makruf Abduljalil ; editor, Ayip Syafruddin - ABDUL AZIZ BIN ABDULLAH BIN BAZ, Syaikh; Syafruddin, Ayip; Abduljalil, Makruf; Muhammad bin Shalih Al-Utsaimin (Pustaka Mantiq, 1995)
93 hlm. 16 cm.